Clinicopathological Profile and Treatment Stratification in Urinary Bladder Cancer: A Retrospective Study - Hanan M Garalla; Khaled M Darraz; Amal Elarebe; Ahmed Khaled Darz (Benghazi University Medical Journal, 2026)
Background: Urinary bladder cancer (UBC) exhibits marked heterogeneity in its clinicopathological characteristics, which directly influence treatment strategies and disease behavior. Understanding the correlation between pathological features and therapeutic approaches is crucial for optimizing patient management. Aim: To evaluate the interplay between clinicopathological characteristics and treatment modalities in urinary bladder cancer and their implications for tumor behavior and clinical decision-making. Materials and Methods: This retrospective cohort study was conducted at the Department of Urology, Faculty of Medicine, Benghazi, in collaboration with the National Cancer Center, from January 2022 to December 2025. A total of 100 cases diagnosed via transurethral resection of bladder tumor (TURBT) and radical cystectomy were included. Non-neoplastic lesions were excluded. Data on demographics, clinical presentation, histopathology, tumor stage, grade, invasion status, and treatment were analyzed. Chi-square tests were used for associations, with p < 0.05 considered significant, with the calculation of odds ratios (OR) and 95% confidence intervals (CI). Results: The data showed marked male predominance (91%; ratio 10.1:1) with a mean age of 60.2 ± 4.4 years. Most patients (90%) were aged 40–80 years. Painless hematuria (58%) and smoking (87%) were predominant. Urothelial carcinoma accounted for 92% of cases. Muscle-invasive disease was present in 62%, and 66% had high-grade tumors. A significant association was observed between tumor grade and muscle invasion (χ² = 15.60, p < 0.001), with high-grade tumors being significantly more likely to present with invasive disease (OR = 5.73; 95% CI: 2.33–14.10).Treatment showed a significant association with disease category (χ² = 95.05, p < 0.001). Conclusion: UBC in this region is characterized by advanced presentation and aggressive biological behavior. The strong correlation between high grade and invasion emphasizes the urgent need for earlier detection strategies and tobacco cessation programs.